Efforts to Improve the Mathematics Learning Process at MTsN 1 Southeast Aceh - Sunardi (Yayasan Zia Salsabila, 2023)
This study aims to determine students' understanding of how to think and learning outcomes in the process of learning mathematics in an effort to increase students' interest in learning mathematics. This study used a qualitative method and the subjects were taken by class students at MTsN 1 Southeast Aceh. Collecting research data using observation techniques, interviews, and documentation. This study concluded that the results of the interview process at the low and high grade levels were that many of them lacked understanding and lack of interest in learning mathematics in madrasas. The factors that hinder the process of learning mathematics, including the lack of interest and motivation of students towards learning and the methods used by the teacher are too monotonous so that it makes students less interested and excited to take part in the process of learning mathematics.